Biodiversity of brewery yeast strains and their fermentative activities. Issue 1 (4th November 2014) - Berlowska, Joanna; Kregiel, Dorota; Rajkowska, Katarzyna
Abstract We investigated the genetic, biochemical, fermentative and physiological characteristics of brewery yeast strains and performed a hierarchical cluster analysis to evaluate their similarity. We used five different ale and lager yeast strains, originating from different European breweries and deposited at the National Collection of Yeast Cultures (UK). Ale and lager strains exhibited different genomic properties, but their assimilation profiles and pyruvate decarboxylase activities corresponded to their species classifications. The activity of another enzyme, succinate dehydrogenase, varied between different brewing strains. Our results confirmed that ATP and glycogen content, and the activity of the key metabolic enzymes succinate dehydrogenase and pyruvate decarboxylase, may be good general indicators of cell viability. However, the genetic properties, physiology and fermentation capacity of different brewery yeasts are unique to individual strains. Copyright © 2014 John Wiley & Sons, Ltd.